Risk factors associated with blood vitamin D levels in COVID-19 patients - Tyani Khoerunissa; Dessy Hermawan; Nurul Aryastuti; Nova Muhani; Syafik Arisandi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
The two main factors associated with infectious diseases are the presence of antigens that enter the body and the immune system. It has been recently reported that vitamin D may be associated with the immune system. This study aimed to analyze the relationship between blood vitamin D levels and the occurrence of COVID-19 infection. This study used a cross-sectional approach for analytical survey research. The population in this study were all lecturers at Malahayati University. The total population participating in this study was 62 lecturers at Malahayati University. Direct competitive chemiluminescence immunoassays were used to measure vitamin D levels, while interviews collected other variables. Logistic regression analysis has been used to analyze the collected data. Results: There was a significant relationship between vitamin D levels and the incidence of COVID-19 infection (p= 0,020; OR= 4,9) & the habit of always wearing long clothes for more than 10 years is significantly related to blood vitamin D levels (p= 0,021; OR= 5,07). In conclusion, the lower the vitamin D level, the greater the risk of being infected with COVID-19, and the longer you wear long clothes, the higher the risk of having low blood vitamin D levels.